Technology Entrepreneurship Project (ENT 600) : Samsung Electronic Malaysia [SME] / Umi Nasuha Ismail - Ismail, Umi Nasuha (2021)
Samsung Malaysia Electronic (SME) Sdn Bhd Company is producing a lot electronic product such home appliance and mobile gadget. This Samsung Company founded by Lee Byung-Chull (1910-1987) in Taegu, Korea on March 1, 1938. The research that I carry is located at George Town Penang, Malaysia, which is the one of their company. One of the producing product by their company is refrigerator. The objective of this study are to search the problem that Samsung refrigerator faced and provide better solution to overcome the problem and suggest a recommendation to the company in order to become a successful company. After doing company research, there are several problems founded about Samsung refrigerator. The major problem Samsung refrigerator is icemakers because it starts to freeze up quite often to the extent that you cannot dispense any ice at all hence becoming completely unusable, icemaker’s motor is quite loud when making the ice and don’t have instaView door in door design. The first alternative is create automatic temperature and also create a button at the refrigerator when we want use immediately. The second alternative is changing with Vremi Countertop icemaker. This can make up to 26 pounds of ice per day in a 24-hour period. The last alternative is create instaView door in door. The InstaView door in door need a glass panel that lights up the inside of the fridge with put your finger. Thus, this study come out with a recommendation to choose one of the alternatives. This study suggested to choose create instaView door in door. This is because this solution can solve household problem.